2005
DOI: 10.1103/physrevc.72.054601
|View full text |Cite
|
Sign up to set email alerts
|

Airy minima in the scattering of weakly bound light heavy ions

Abstract: We reanalyze the existing 6 Li + 12 C elastic scattering angular distributions for incident energies ranging from a few MeV to 318 MeV within the frame of the optical model. Despite the important breakup effects expected in the scattering of such a fragile projectile, the system is found to display a surprising transparency. Indeed the barrier-wave/internal-wave decomposition of the elastic scattering amplitude reveals that a substantial part of the incident flux that penetrates the nuclear interior reemerges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…First, the data were analyzed in terms of conventional optical-model (OM) calculations using both volume-type Woods-Saxon(WS) and double-folding nuclear potentials (plus Coulomb potentials due to uniform charged spheres). The WS potential parameters are listed in Table I and were taken from references [15][16][17]. The results of the OM calculations can be seen in Figs.…”
Section: Introductionmentioning
confidence: 84%
“…First, the data were analyzed in terms of conventional optical-model (OM) calculations using both volume-type Woods-Saxon(WS) and double-folding nuclear potentials (plus Coulomb potentials due to uniform charged spheres). The WS potential parameters are listed in Table I and were taken from references [15][16][17]. The results of the OM calculations can be seen in Figs.…”
Section: Introductionmentioning
confidence: 84%
“…However, similar to the rainbow in elastic scattering, the study of the inelastic rainbow scattering will be very useful in understanding the interaction potential for the inelastic channels [5,[10][11][12][13]. The mechanism of the nuclear rainbow and the Airy structure in inelastic scattering has been studied for the α + 40 Ca and 6 Li + 12 C systems by using a phenomenological form factor [14,15]. On the other hand, from the viewpoint of a nuclear structure study it has recently been shown that inelastic nuclear rainbow scattering is powerful in understanding the α-cluster structure of the excited states of the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic rainbow scattering has also been especially powerful in understanding the highly excited cluster structure near and above the threshold energy, such as the α particle condensation of the Hoyle state in 12 C and the Hoyle-analog state in 16 O [21][22][23][24][25]. A recent systematic study of the evolution of the Airy structure in inelastic scattering for the typical α+ 16 O system [26] showed that the cluster structure with core excitation in 20 Ne near the threshold energy region and the inelastic nuclear rainbow scattering can be understood in a unified way by using reliable interaction potentials for the inelastic channels. This urges us to study inelastic rainbow scattering with heavy ions in order to determine the interaction potentials in inelastic channels, which will make it possible to understand the molecular structure with core excitation, for which phenomenological shallow potentials have been used widely instead of a deep potential [27].…”
Section: O+mentioning
confidence: 99%
“…The rainbow in inelastic rainbow scattering makes it possible to understand the interaction potential for the inelastic channels up to the internal region. For typical α+ 40 Ca and 6 Li+ 12 C systems [18,19], the mechanism of the nuclear rainbow and the Airy structure in inelastic scattering has been studied [19,20]. Inelastic rainbow scattering has also been especially powerful in understanding the highly excited cluster structure near and above the threshold energy, such as the α particle condensation of the Hoyle state in 12 C and the Hoyle-analog state in 16 O [21][22][23][24][25].…”
Section: O+mentioning
confidence: 99%